Strategies for Strengthening Ecological Citizenship in the Sendi Indigenous People of Mojokerto Regency - Maulana, Bariq; ., Triyanto; Triastuti, Rini (KnE Social Sciences, 2024)
Environmental degradation is currently causing many hydrometeorological disasters. Ecological Citizenship as part of the concept of civic education has the aim of forming smart citizens with environmental character. This study analyzes the form of strategies to strengthen ecological citizenship in Sendi indigenous peoples of Mojokerto Regency along with the obstacles and challenges they face in strengthening environmental awareness based on local wisdom. The study uses qualitative research methods with a case study design. Data were collected through direct observation in the environment where the joint indigenous community lives, interviews with kasepuhan, pamengku adat, and members of the Sendi indigenous people, and documentation. Data were analyzed using interactive data analysis methods. It was found that the Sendi indigenous people have a strategy to strengthen Ecological Citizenship based on local wisdom, namely sengkalaning sendi, which regulates relationships with nature and the environment, in collaboration with various stakeholders and NGOs such as Walhi and PPLH. The obstacles encountered by the Sendi indigenous people are mainly internal and external factors. Keywords: ecological citizenship, Sendi indigenous people